Politiche di gestione della risorsa idrica sotterranea a fini irrigui. Analisi delle preferenze degli agricoltori - Giacomo Giannoccaro; Ruggiero Sardaro; Rossella de Vito; Luigi Roselli; Bernardo C. de Gennaro (Economia Agro-Alimentare, 2020)
The overexploitation of groundwater for irrigation purposes is a general problem affecting the management of common resources. The objective of this study was to analyze some of the policy options when facing this issue. A choice experiment was performed in order to elicit farmers’ stated preferences for four policy instruments, namely i) implementation of a compulsory measurement system of groundwater extraction; ii) improved monitoring of rural areas in order to limit illegal access to groundwater; iii) reforming the groundwater tax system; iv) increasing the supply of reclaimed wastewater for irrigation. A survey was conducted in the Puglia region on a representative sample of 187 farmers, selected in the main hot-spot irrigated areas. A Random Parameter Logit Model was estimated using two covariates (i.e. size of irrigable farmland and farmers’ awareness of groundwater shortage). Findings highlighted the farmers’ preference for increasing the supply of water for irrigation (i.e. wastewater supply). Among the measures aiming to handle groundwater demand for irrigation, the respondents positively valued the enhancement of rural area monitoring to prevent illegal access, but they rejected a compulsory groundwater metering system. Finally, the methodological approach proved to be an effective tool to improve policy design, making the decisionmaking process more participatory.